SMARTS (Systematic Monitoring of Adverse events Related to TreatmentS): The development of a pragmatic patient-completed checklist to assess antipsychotic drug side effects. (February 2014) - Haddad, Peter M; Fleischhacker, W Wolfgang; Peuskens, Joseph; Cavallaro, Roberto; Lean, Michael EJ; Morozova, Margarita; Reynolds, Gavin; Azorin, Jean-Michel; Thomas, Pierre; Möller, Hans-Jürgen
Objectives: Antipsychotic drug side effects are common and can cause stigmatisation, decreased quality of life, poor adherence, and secondary morbidity and mortality. Systematic assessment of anticipated side effects is recommended as part of good clinical care, but is uncommon in practice and patients may not spontaneously report side effects. We aimed to develop a simple patient-completed checklist to screen systematically for potential antipsychotic side effects. Methods: The SMARTS checklist was developed over a series of group meetings by an international faculty of 12 experts (including psychiatrists, a general physician and a psychopharmacologist) based on their clinical experience and knowledge of the literature. The emphasis is on tolerability (i.e. assessment of side effects that 'trouble' the patient) as subjective impact of side effects is most relevant to medication adherence. The development took account of feedback from practising psychiatrists in Europe, the Middle East and Africa, a process that contributed to face validity. Results: The SMARTS checklist assesses whether patients are currently 'troubled' by 11 well-established potential antipsychotic side effects. Patients provide their responses to these questions by circling relevant side effects. An additional open question enquires about any other possible side effects. The checklist has been translated into Italian and Turkish. Conclusions: The SMARTS checklist aims to strike a balance between brevity and capturing the most common and important antipsychotic side effects. It is appropriate for completion by patients prior to a clinical consultation, for example, in the waiting room. It can then form the focus for a more detailed clinical discussion about side effects. It can be used alone or form part of a more comprehensive assessment of antipsychotic side effects including blood tests and a physical examination when appropriate. The checklist assesses current problems and can be used longitudinally to assess change.